Serpentine gallery pavilions - Jodidio, Philip, 1954- (Köln : Taschen, 2011)
The pavilions in the Programme that was conceived in 2000 by the Serpentine Director Julia Peyton-Jones, are the work of international architects or design teams who at the time of the Serpentine's invitation have not completed a building in England. A maximum of six months from invitation to completion is allotted. The only architecture program of its type in the world, the Serpentine Gallery Pavilions attract up to 250,000 visitors each summer. The Serpentine Pavilion is regularly ranked in the top 5 most attended architecture and design exhibitions worldwide in The Art Newspaper's annual survey of museums and galleries visitor figures.
Introduction: Interview with Julia Peyton-Jones and Hans Ulrich Obrist -- Zaha Hadid -- Daniel Libeskind -- Toyo Ito -- Oscar Niemeyer -- MVRDV -- Álvaro Siza & Eduardo Souto de Moura -- Rem Koolhaas & Cecil Balmond -- Olafur Eliasson & Kjetil Thorsen -- Frank O. Gehry -- Sanaa -- Jean Nouvel.
English, French and German.
Keywords: Serpentine Gallery; Architecture, Modern -- 21st century; Architectuur; Arts, Modern -- 21st century; Bouwkunst; Buildings, Temporary -- England -- London; Pavilions -- England -- London